SEMINAR TENTANG IDENTIFIKASI DRPs PADA PASIEN GERIATRI YANG MENERIMA RESEP POLIFARMASI PADA PENYAKIT STROKE - Yanna Rotua Sihombing; Asti Pratiwi; Yosi Darmirani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
This study aims to determine the presence of DRPs in geriatric patients who are prescribed polypharmacy in stroke patients. This study is a prospective study with data presented descriptively. Data were obtained from medical records, drug information cards and patient interviews. The results of this study were 41 patients who were used as subjects. There were 3 people (7.32%) experienced DRPs and 38 people (92.68%) did not experience DRPs. Of the seven categories of DRPs, there were only 2 categories of DRPs, category 1, namely congenital drug therapy that was not localized (2.44%) and category 2, which was the incidence of too high a dose (4.88%)